2020
DOI: 10.1108/jiabr-03-2017-0031
|View full text |Cite
|
Sign up to set email alerts
|

Incentives for conventional banks for the conversion into Islamic banks: evidence from Bangladesh

Abstract: Purpose The skyrocketing rise of Islamic banking is noticeable in not only Islamic countries but also non-Islamic countries during the past few decades. Many conventional banks have started Islamic banking generally by maintaining separate branches/windows and occasionally by pursuing a complete conversion strategy. Following the global trend, two of the full-fledged Islamic banks adopted a conversion strategy consecutively in 2004 and 2008 in Bangladesh. The number of the conversion case is still limited. At … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
11
1

Year Published

2021
2021
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(16 citation statements)
references
References 20 publications
3
11
1
Order By: Relevance
“…Islamic Commercial Bank chooses customers or mudharib with high eligibility to be funded so that channel financing can reduce financing risk (NPF). This finding is also linear with the findings of Mutamimah & Saputri (2022) and contradicts previous findings (Adzimatinur & Manalu, 2020;Omer Mustafa, 2020;Suzuki et al, 2020), which reveals a significant positive relationship between Mudharaba financing and financing risk.…”
Section: Discussioncontrasting
confidence: 66%
See 2 more Smart Citations
“…Islamic Commercial Bank chooses customers or mudharib with high eligibility to be funded so that channel financing can reduce financing risk (NPF). This finding is also linear with the findings of Mutamimah & Saputri (2022) and contradicts previous findings (Adzimatinur & Manalu, 2020;Omer Mustafa, 2020;Suzuki et al, 2020), which reveals a significant positive relationship between Mudharaba financing and financing risk.…”
Section: Discussioncontrasting
confidence: 66%
“…Profits from the Mudharaba contract will be shared in a fixed ratio, while losses will be borne by the Islamic Bank (Fianto et al, 2019). Mudharaba financing is considered to be riskier than Musharaka financing, and the two contracts have a significant impact on non-performing financing (Adzimatinur & Manalu, 2020;Omer Mustafa, 2020;Suzuki et al, 2020). This is contrary to research findings from Warninda et al (2019) and (Mutamimah & Saputri, 2022), which found no relationship between the two and even a negative effect.…”
Section: Literature Review the Effect Of Mudharaba Musharaka And Mura...mentioning
confidence: 93%
See 1 more Smart Citation
“…The asset value of Subsidiary Unit or Usaha Unit Syariah (UUS) has reached 50% of Conventional Commercial Banks' total asset value (Yuspin et al, 2020). Something similar happened in Bangladesh, where many conventional banks have also started Islamic banking by maintaining separate branches/windows and sometimes carrying out a complete conversion strategy (Suzuki et al, 2020). Islamic banking's prospect depends on the consumer's knowledge of Islamic banking (Ezeh & Nkamnebe, 2019b;Abbas & Shirazi, 2015).…”
Section: Literature Reviewmentioning
confidence: 99%
“…Sen et al (2020) identified that high-profit ratio, ATM facility, available services, lower operating cost and lower deposit fee are the important factors influencing the customers toward Islamic banks in Bangladesh. Suzuki et al (2020) revealed that Islamic banks are becoming popular to the people of Bangladesh because of some advantages, for instance, fewer reserve requirements, protective regulation, suitable credit strategy and participatory financing. Ullah and Khanam (2018) exposed that Shariah compliance influenced the internal and external strengths of Islamic banks for maintaining better financial performance in Bangladesh.…”
Section: Introductionmentioning
confidence: 99%